Independence of Tolgau: Fundamentals and Current Trends - Ryskulbekova С.; Duysengazy, C. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2019)
Written works about independence are works that are filled with pathos. They are based on the idea of achieving freedom, on the idea of eternal country. Therefore, writing about independence requires tremendous responsibility and confidence. The article discusses the topic of independence which is now widely considered. A large amount of theoretical literature on the themes of the article was studied and analyzed by various scientists. It is analyzed in the context of modern life, the creation of modern non-independence, ideology of indifference. Modern contexts are discussed in Kazakh poetry and new conceptions of indifference. The relation and the difference between verse and tolgau are separate. In connection with the theme of independence, poetic compositions were subjected to relative analysis and a final report was compiled